Designing a Web-Based Inventory System Using the Agile Method for Management Efficiency in Buduran District - Ratih Sri Yunarti; Nuril Lutvi Azizah; Ade Eviyanti; Hamzah Setiawan (SaNa: Journal of Blockchain, NFTs and Metaverse Technology, 2025)
The rapid development of information technology has had a major impact on various aspects of government administration, including asset and inventory management. In Buduran District, Sidoarjo Regency, inventory data recording is still done manually. This unintegrated system often causes data inconsistencies, difficulties in tracking goods, and inefficiency in the reporting and auditing processes. To overcome these problems, this study designed a web-based inventory information system using the Agile development method. The Agile method allows for gradual system development with user feedback at each iteration, making the system more adaptive to field needs. This system enables digital inventory recording, tracking, and reporting, thereby improving the accuracy, efficiency, and transparency of asset management. Testing using the Black Box method showed that all system features, both from the user and admin sides, worked as expected with a 100% success rate. In addition, the results of the User Acceptance Testing (UAT) showed a user satisfaction rate of 95.6% from five respondents, consisting of two administrators and three staff members. The developed system is expected to improve operational effectiveness and support better decision-making in asset management at the sub-district level.